The Activities of Russian Libraries in the Dissemination of Scientific Knowledge - L. K. Kurmysheva (Библиосфера)
The issue of spreading scientific knowledge is relevant at the present stage of development of society. The library, as the most accessible cultural institution, is able to ensure the dissemination of this knowledge in all social strata of the population. The purpose of the article is to study the intensity and forms of events of scientific, popular science and educational content of federal, republican, regional and regional Russian libraries, reflected on official websites. The article deals with information about the popular scientific activities of the leading Russian libraries. The ongoing projects and mass events of scientific, popular science and educational content are described. Content analysis has become the main method of collecting information. The study was performed at the end of 2022 and the beginning of 2023. The site analysis showed that libraries, as cultural institutions, hold a sufficient number of various mass events in the form of lectures, master classes, intellectual games, quizzes, but the scientific or popular science content of these events is not always confirmed. Basing on two stages of the study the following conclusions were made: science promotion activities were present in an average of 33 % of the libraries surveyed. The most popular form of such events was a lecture with the participation of a guest lecturer. Most of the activities were aimed at young people.